2023
DOI: 10.1088/1361-6528/acca8b
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer WSe2/ZnO heterojunctions for self-powered, broadband, and high-speed photodetectors

Abstract: Self-powered broadband photodetectors have attracted great interest due to their applications in biomedical imaging, integrated circuits, wireless communication systems, and optical switches. Recently, significant research is being carried out to develop high-performance self-powered photodetectors (SPPDs) based on thin 2D materials and their heterostructures due to their unique optoelectronic properties. Herein, a vertical heterostructure based on p-type 2D WSe2 and n-type thin film ZnO is realized for photod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The main performance data of PdTe 2 and ZnO-based photodetectors are listed in Figure e and Table S1. Compared to the PdTe 2 -based device, our device has a 10–10 6 higher response time and an extended detection range to UV. ,, Compared to the ZnO/TMDC heterojunction device, the ZnO@PdTe 2 /Si heterojunction has a wider response range (254 nm–1.55 μm), and the D * and response/recovery times are improved by 10–10 3 . …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The main performance data of PdTe 2 and ZnO-based photodetectors are listed in Figure e and Table S1. Compared to the PdTe 2 -based device, our device has a 10–10 6 higher response time and an extended detection range to UV. ,, Compared to the ZnO/TMDC heterojunction device, the ZnO@PdTe 2 /Si heterojunction has a wider response range (254 nm–1.55 μm), and the D * and response/recovery times are improved by 10–10 3 . …”
Section: Resultsmentioning
confidence: 87%
“…PdTe 2 and ZnO lattice spacings are 0.20 and 0.28 nm, respectively, with PdTe 2 being dominantly oriented (001). Figure S3a,b,d,e shows the results of X-ray photoelectron spectroscopy (XPS), in which peaks at about 336.25, 341.49, 575.54, 585.94, 532.81, 1022.98, and 1046.09 eV are attributed to the Pd 3d 5/2 , Pd 3d 3/2 , Te 3d 5/2 , Te 3d 3/2 , O 1s, Zn 2p 3/2 , and Zn 2p 1/2 orbitals, respectively. , In addition, the X-ray diffraction (XRD) patterns of PdTe 2 and ZnO show significant diffraction peaks (Figure S3c,f).…”
Section: Resultsmentioning
confidence: 99%
“…Responsivity values of 0.03 and 0.01 mA·W −1 are obtained for 532 and 640 nm, respectively ( Figure 6b ). Since detectivity and photoconductive gain depend on the responsivity [ 52 ], the values of G and D are 0.69 × 10 −4 and 17.1 × 10 6 Jones for λ = 532 nm, and 0.19 × 10 −4 and 5.34 × 10 6 Jones for λ = 640 nm, which corresponds to the relatively low responsivity values at these wavelengths. Thereby, it can be concluded that the operation range of the CuO NPs/ZnO NRs photodetector could be extended to the visible region.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, TMDC/ZnO heterostructures have been focused on self‐powered and broadband detection 177–179 . In a recent study, a n‐MoS 2 /n‐ZnO heterojunction with type II band alignment was developed by depositing MoS 2 film onto ZnO film 180 .…”
Section: Integrating Tmdc With 3d Semiconductor Van Der Waals As Hete...mentioning
confidence: 99%